Pengembangan Citra Sekolah Melalui Manajemen Humas Di Madrasah Aliyah Negeri 4 Kediri - Subakir (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Educational institutions are grown and developed through initiatives, and to guide the community, so that the existence of public relations management in the development of educational institutions is important. This article aims to provide the concept of public relations management techniques in the development of educational institutes in Indonesia, as well as how to apply them, the problems encountered, and how to solve these problems. It is hoped that the results of this research can broaden the horizons of educational institution managers so that this program can run effectively and efficiently, and realize the development of educational institutions in a broad sense. Community relations planning in an effort to improve the image of school institutions at state madrasah aliyah 4 Kediri by involving all school managers, scheduling all good and detailed community relations and planning activities through an annual meeting program. the implementation of public relations at state madrasah aliyah 4 Kediri is carried out in accordance with the plan in which the tasks of public relations 9 all activities in the madrasa are publicly known and the implementation of human management at educational institutions is a communication link or an extension of information to be conveyed to the community. This research was conducted at MAN 4 Kediri. This research was carried out using a descriptive qualitative approach, and in collecting data researchers used interview techniques, observation and documentation studies. The main subjects in this study were public relations, school principals, teachers and students